The illicit enrichment law and financial disclosure system in Malaysia - Muhammad Azman Ng, Noratikah; Ayub, Zainal Amin (Global Academic Excellence, 2018)
This article discusses the issue of corruption in Malaysia and the anti-corruption law in Malaysia which is the Malaysian Anti-Corruption Commission Act 2009 and Penal Code (Act 574). This article intends to highlight the main topic of concern which is the illicit enrichment crime or living beyond means among public officials in Malaysia. Besides, there is also a lack of legislation and enforcement on the financial disclosure system or asset declaration system by the public officials in Malaysia. The financial disclosure system in Malaysia must be strengthened and be taken seriously in monitoring the public official’s wealth to prevent any possibility of illicit enrichment. Furthermore, this article will adopt the doctrinal approach and qualitative study as a research methodology. The researcher will use the semi-structured interview in collecting the data in order to develop the validity and authenticity of the results. The semi-structured interview will make the researcher knows deeper and complete understanding of the experiences, opinions, and attitudes of the respondents towards the issue of illicit enrichment. This article will contribute significantly towards strengthening the existing law of prevention of corruption in Malaysia, thereby will help to reduce corruption rate especially those involved with illicit enrichment crime.